2020
DOI: 10.3389/fcell.2020.00801
|View full text |Cite
|
Sign up to set email alerts
|

HGF/c-Met Axis: The Advanced Development in Digestive System Cancer

Abstract: Numerous studies have indicated that abnormal activation of the HGF/c-Met signaling pathway can lead to cell proliferation, invasiveness, and metastasis of cancers of the digestive system. Moreover, overexpression of c-Met has been implicated in poor prognosis of patients with these forms of cancer, suggesting the possibility for HGF/c-Met axis as a potential therapeutic target. Despite the large number of clinical and preclinical trials worldwide, no significant positive success in the use of anti-HGF/c-Met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 113 publications
1
17
0
Order By: Relevance
“…In previous studies, the HGF/c-Met signaling pathway is a key factor in tumor progression [8,22]. We found that MACC1 is an important activator of c-Met.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In previous studies, the HGF/c-Met signaling pathway is a key factor in tumor progression [8,22]. We found that MACC1 is an important activator of c-Met.…”
Section: Discussionsupporting
confidence: 50%
“…Under normal physiological conditions, HGF/c-Met can mediate embryonic development, cell proliferation, injured tissue repair, and neuromuscular formation [7]. A large number of studies have shown that the overactivation of c-Met may initiate the transformation of normal cells to tumor cells and further promote the occurrence of subsequent events such as invasion, metastasis, and diffusion [8]. c-Met is the encoding HGF receptor gene, located in 7q21-q31 on human chromosome 7; is a transmembrane receptor protein tyrosine kinase; and is expressed mainly in the epithelial tissue [9].…”
Section: Introductionmentioning
confidence: 99%
“…In non-malignant situations, hepatocyte growth factor (HGF)/mesenchymal-epithelial transition factor (MET) signaling is essential for embryogenesis, muscle development, nervous system formation, hematopoietic cell differentiation, and bone remodeling [19,20]. In malignant disease, the activation of the HGF/MET signal pathway results in cell proliferation, survival, inhibition of apoptosis, migration, invasion, and metastasis [21][22][23]. This is also true for UM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, among the reported c-Met inhibitors, crizotinib and cabozantinib are approved for the treatment of nonsmall-cell lung cancer and medullary thyroid cancer. 22 29 To date, no selective c-Met kinase inhibitors have been approved for clinical use. Based on the inhibitory results from the ELISA kinase assay, chalcone-1,3,4-thiadiazole hybrid ZW97 selectively and potently inhibited c-Met kinase with an IC 50 of 27.96 nM.…”
Section: Discussionmentioning
confidence: 99%